UTILIZATION OF SERVICES OF HOMEOPATHIC PRACTITIONERS AMONG PATIENTS IN KARACHI, PAKISTAN - Qidwai, Waris (Journal of Ayub Medical College Abbottabad, 2003)
Background: The practice of homeopathy is becoming very popular. There is a need to study and understand as to why this is happening and to raise debate on the issue. Methods: The study was conducted on patients, visiting the Family Practice Centre, The Aga Khan University, Karachi. A questionnaire was used to collect information on the demographic profile, and the utilization of the services of homeopathic practitioners. The ethical requirements for conducting the study were met. Results: Three hundred and eighty-seven patients were surveyed. The study population included more women then men, with average age of 32.6 years. The majority was married, well educated, in private and government service, students or housewives. A substantial 36.4% of the respondents had used the services of Homeopathic practitioners for various ailments. The five main ailments for consulting them were skin diseases, influenza, headache, gastro-intestinal and musculo-skeletal problems. The main reason for consulting Homeopathic practitioners was the ’˜recommendation of others’. The reasons for not consulting them were the ’˜lack of belief in them’, ’˜allopaths were considered more effective’, ’˜Homeopathic practitioners were considered unscientific’, and ’˜were not considered a treatment option’. Among those who had consulted Homeopathic practitioners in the past, a substantial 67% of them were willing to consult them again in future. Conclusion: We have found a substantial utilization of services of Homeopathic practitioners among patients seeking allopathic treatment. Further studies are strongly recommended to study the need, utilization and organization of services offered by Homeopathic practitioners and the reasons for their popularity Key-words: Homeopathy; Complementary therapies; Alternative medicine